MOOCs, openness and changing educator practices: An Activity Theory case study - Czerniewicz, Laura; Glover, Michael; Deacon, Andrew; Walji, Sukaina (Proceedings of the International Conference on Networked Learning, 2016)
The practices and perceptions of educators formed through the creation and running of a Massive Open Online Course (MOOC) provide a case study of how educators understandings of ‘openness’ change (Beetham et al 2012, p 3). We are interested in how educators engage with open education resources (OER) and openness as part of developing open online courses, and how this informs their practices and attitudes afterwards. Deepening understandings of these changes is important for informing strategies involving helping educators in adopting productive open educational practices. Our research question is how do educators’ practices change or not change when using - or not using - OER in and as a MOOC? We are interested in whether and why educators adopt open practices in their MOOCs. We employ an Activity Theory (AT) conceptual framework as a heuristic tool to track and thickly describe educators’ practices and perceptions. This frame enables us to locate educators’ practices - in a context of mediating nodes, i.e., tools/artefacts, rules, divisions of labour, and community - as they strive towards and consider their object. The object upon which the educators act is the development of a new interdisciplinary field. We focus on the role of two mediating artefacts introduced into the activity system, namely Creative Commons (CC) licenses and the ‘MOOC design’. We describe how the open aspect of these artefacts mediate and affect educator’s perceptions, attitudes and educational practices in the context of their object-directed activity system. We draw predominantly on semi-structured interviews with the MOOC lead educators and the MOOC learning designers. Interviews were conducted at two time intervals, before and after the MOOC has run. From this we craft two activity systems. We have categorised our findings according to Beetham et al’s dimensions of open practices. Further, two broad themes emerged from the data analysis. These are Affordances of the MOOC and Reflection on educational practices.